A Window into the Workings of anti-B18H22 Luminescence-Blue-Fluorescent Isomeric Pair 3,3'-Cl2-B18H20 and 3,4'-Cl2-B18H20 (and Others) - Ehn, Marcel; Bavol, Dmytro; Bould, Jonathan; Strnad, Vojtěch; Litecká, Miroslava; Lang, Kamil; Kirakci, Kaplan; Clegg, William; Waddell, Paul G; Londesborough, Michael G S (Molecules (Basel, Switzerland), 2023)
The action of AlCl3 on room-temperature tetrachloromethane solutions of anti-B18H22 (1) results in a mixture of fluorescent isomers, 3,3'-Cl2-B18H20 (2) and 3,4'-Cl2-B18H20 (3), together isolated in a 76% yield. Compounds 2 and 3 are capable of the stable emission of blue light under UV-excitation. In addition, small amounts of other dichlorinated isomers, 4,4'-Cl2-B18H20 (4), 3,1'-Cl2-B18H20 (5), and 7,3'-Cl2-B18H20 (6) were isolated, along with blue-fluorescent monochlorinated derivatives, 3-Cl-B18H21 (7) and 4-Cl-B18H21 (8), and trichlorinated species 3,4,3'-Cl3-B18H19 (9) and 3,4,4'-Cl3-B18H19 (10). The molecular structures of these new chlorinated derivatives of octadecaborane are delineated, and the photophysics of some of these species are discussed in the context of the influence that chlorination bears on the luminescence of anti-B18H22. In particular, this study produces important information on the effect that the cluster position of these substitutions has on luminescence quantum yields and excited-state lifetimes.
Keywords: Luminescence; anti-B18H22; cluster boron hydrides; Molecular Structure; halogenation; chlorination; excited-state lifetime; fluorescence; luminescence; quantum yield; isomerie; Isomerism; substitution; Halogenation; luminiscence; halogenace; molekulární struktura